Nanostructures and impurity centers in cryogenic environments - McCaffrey , John; Savchenko, Elena (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2025)
Studies of matter at extremely low temperatures are providing new physico-chemical insights into their behaviour under astronomical conditions but also yielding predictions which guide the fabrication of new materials of technological interest. These works involve cooled rare gas clusters generated in the gas phase and also the condensed phase environments of low cryogenic solids – historically known as matrix-isolation spectroscopy. The majority of these studies very effectively rely on input from quantum chemical calculations to provide powerful interpretation of the energy resolved spectroscopic observations made at low temperature of the underlying inter-atomic and inter-molecular interactions.